2006
DOI: 10.1093/ajcn/83.6.1467s
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, interconversion, and dose response of n−3 fatty acids in humans

Abstract: n-3 Fatty acids have important visual, mental, and cardiovascular health benefits throughout the life cycle. Biodistribution, interconversion, and dose response data are reviewed herein to provide a basis for more rational n-3 dose selections. Docosahexaenoic acid (DHA) is the principal n-3 fatty acid in tissues and is particularly abundant in neural and retinal tissue. Limited storage of the n-3 fatty acids in adipose tissue suggests that a continued dietary supply is needed. A large proportion of dietary alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

45
816
8
37

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 993 publications
(920 citation statements)
references
References 96 publications
45
816
8
37
Order By: Relevance
“…Changes in the FA composition of tissues from rabbit (Bernardini et al, 1999), other animals (Wood and Enser, 1997;Enser et al, 2000;Bou et al, 2006b) and humans (Arterburn et al, 2006) have been reported as a result of varying the FA profile of diets. In our study in rabbits, the content of trans FA in plasma and liver and the content of MUFA in liver decreased, while total PUFA in liver increased (Tables 1 and 2) as BT in feeds was replaced by increasing doses of n-6-or n-3-rich vegetable fat .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in the FA composition of tissues from rabbit (Bernardini et al, 1999), other animals (Wood and Enser, 1997;Enser et al, 2000;Bou et al, 2006b) and humans (Arterburn et al, 2006) have been reported as a result of varying the FA profile of diets. In our study in rabbits, the content of trans FA in plasma and liver and the content of MUFA in liver decreased, while total PUFA in liver increased (Tables 1 and 2) as BT in feeds was replaced by increasing doses of n-6-or n-3-rich vegetable fat .…”
Section: Resultsmentioning
confidence: 99%
“…However, the effectiveness of the synthesis of DHA from linolenic acid in animals and humans is controversial, as it has been reported to be limited (Cherian and Sim, 1995;D'Arrigo et al, 2002;Hoz et al, 2003;Burdge and Calder, 2005b;Nuernberg et al, 2005). This has been related to the last step in the biosynthesis pathway of DHA, a b-oxidation of C24:6n-3 which involves translocations between the endoplasmic reticulum and peroxisomes of both DHA and its precursor (C24:6n-3) (Burdge and Calder, 2005b;Arterburn et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…patients without CHD of 'at least two (preferable oily) fish meals per week' or approximately 500 mg EPA + DHA/d; while for patients with CHD an EPA + DHA intake of 1 g, preferably from oily fish is recommended (52) .…”
Section: Dietary Groups Dietary Groupsmentioning
confidence: 99%
“…n-3 LC PUFA supplements might help to reduce cardiovascular risks by lowering the risk of sudden death of people with a history of cardiovascular problems (4) . Dietary n-3 LC PUFA and n-3 LC PUFA supplements have been demonstrated to be linked with n-3 LC PUFA concentrations in blood, plasma, tissues or human milk, being responsible for beneficial effects on visual and mental health and neurodevelopment (5,6) .Nevertheless, at present, the respective mechanism of action of each of EPA and DHA is debatable. As described in the Symposium 'n-3 fatty acids: recommendations for therapeutics and prevention' convened by the Institute for Human Nutrition of Columbia University on 21 May 2005 (7) , confusion exists about the recommendations and the biological link between intake and health.…”
mentioning
confidence: 99%